Evaluating the transition of adolescents and young adults with palliative care needs from pediatric to adult care - Emma W. Healy; Natasha Z. Piracha (Health Care Transitions, 2024)
Background: The transition from pediatric to adult healthcare poses significant challenges for adolescents and young adults (AYA), especially those with chronic conditions, yet most children receive inadequate transition preparation. Research on the transition for patients receiving palliative care services is particularly limited. We sought to address this gap in the literature. Methods: Young adults aged 18 to 35 years who transitioned from the pediatric setting and received adult palliative care services at an urban academic medical center between the dates of February 1st, 2020 and July 1st, 2022 were identified retrospectively via electronic medical record. Chart review was used to investigate outcomes of interest, including use of pediatric palliative care services and timing of care conversations. Results: Only 23 % of patients interfaced with pediatric palliative care, despite all having childhood diagnoses. Pediatric palliative care exposure was associated with a significantly earlier median age of first adult palliative care encounter (19.63 versus 25.06, p = <0.001). Goals of care discussions, code status conversations, and healthcare proxy documentation occurred earlier if pediatric palliative care was involved (18.9 years versus 25.7 years, p < 0.001; 20.9 years versus 30.0 years, p < 0.001; 20.7 versus 28.9, p < 0.001). Conclusions: Pediatric palliative care services were underutilized in AYA patients, but when used, were associated with earlier adult palliative care encounters, goals of care discussions, code status decisions, and health care proxy identification.